IDENTIFIKASI TINGKAT KESERAGAMAN BATUAN HASIL PELEDAKAN DENGAN METODE KUZ-RAM DAN METODE KOEFISIEN TEKSTUR PADA FRONT I TAMBANG QUARRY PT. SEMEN PADANG - Marchellevandra Gomis; Dedi Yulhendra; Ansosry Ansosry (Journals Mining Engineering : Bina Tambang, 2014)
PT. Semen Padang is one of the greats cement producer industry in Indonesia. PT. Semen Padang has a mining business license for limestone mining at Bukit Karang Putih – Indarung, Padang City, West Sumatera. For getting limestone, PT. Semen Padang used quarry mine system and blasting technique in separating limestone from rock body.In blasting, one of success variable can be viewed from the size of fragmentation and rock uniform level. Size of fragmentation and rock uniform level can be expected with good blast geometry plan. Will be obtained good rock fragmentation, and good uniform level. From the geometry of the blasting used in PT Semen Padang, obtained rock size fragmentation up from 120 cm percentage is 7,84 % with rock uniform level 1,47 and the volume of rock explosed 126 m3 from one blast hole. The percentage of rock filtered is quite good. However, it’s not followed by rock uniform level and rock explosed volume. So that, need for changes blast geometry with ICI – Explosive Method for getting good fragmentation size, good rock uniform level and large rock explosed volume.After calculated and experimented in the site. The most suitable blast geometry is 5 m for spacing and 4 m for burden. So, we can get 210 m3 limestone from one blast hole, with size of rock fragmentation up from 120 cm is 20,92 %, and rock uniform level 1,26. Therefore, will have the impact on increasing the limestones product and rock uniform level better.